2008
DOI: 10.3109/s10165-008-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased percentages of regulatory T cells in peripheral blood of patients with Behcet’s disease before ocular attack: a possible predictive marker of ocular attack

Abstract: The current study investigates the role of regulatory T (Treg) cells in the pathogenesis of ocular attack in patients with Behcet's disease (BD). Nineteen BD patients with ocular complications (BDo), including 11 BD patients with ocular attack (BDa) and eight BD patients with inactive ocular complications (BDi), were studied. Four BD patients without ocular complications (BDwo) were also evaluated as controls. All patients were prospectively followed by our outpatient clinic between autumn 2004 and spring 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…It has been proposed that the dependence on the eye reflects involvement of α-melanocyte-stimulating hormone (α-MSH) present in ocular fluids, but direct evidence to support this is lacking. Importantly, some types of syndromes that include uveitis (such as Behçet and VKH) are reported to be associated with reduced regulatory T cell number and/or function, although the origin of the affected regulatory T cells (natural, induced, or both) is not clear (67,68).…”
Section: Figurementioning
confidence: 99%
“…It has been proposed that the dependence on the eye reflects involvement of α-melanocyte-stimulating hormone (α-MSH) present in ocular fluids, but direct evidence to support this is lacking. Importantly, some types of syndromes that include uveitis (such as Behçet and VKH) are reported to be associated with reduced regulatory T cell number and/or function, although the origin of the affected regulatory T cells (natural, induced, or both) is not clear (67,68).…”
Section: Figurementioning
confidence: 99%
“…In man, nTreg percentages in Behçet's disease patients with ocular complications are decreased before an ocular attack. 13,14 In Vogt Koyanagi Harada (VKH) syndrome, nTreg cells are similarly depleted and also less functional in their suppressive ability, and therefore overall loss of nTregs in active uveitis may contribute to patients' disease susceptibility and severity. 14,15 Immune regulation may not require antigen specificity, as in experimental models of uveitis (EAU), non-retinal antigen-specific nTregs can functionally suppress disease.…”
Section: Understanding Immunopathologymentioning
confidence: 99%
“…In 2001, Baecher-Allan et al demonstrated that, in humans, CD4 + CD25high exhibit all the properties of regulatory T cells (Baecher-Allan et al 2001). We also measured the percentages of CD4 + CD25high T cells as regulatory T cells in patients with Behcet's disease (Nanke et al 2008). In addition, Amadi-Obi et al reported that a major immunological difference between humans and mice is the presence of CD4 + T cells producing IL-17, Th17 cells, in the peripheral blood of healthy humans, but not mice (Amadi-Obi et al 2007).…”
Section: 'Human Osteoclastology' -Difference Between Human and Mouse mentioning
confidence: 96%